Analisis Perhitungan Perencanaan Laba pada UMKM Takoyaki Arone dan Cemal Cemil Indah Depok Menggunakan Metode Break Even Point dengan Memperhitungkan Margin of Safety dan Operating Leverage - Tri Damayanti; Monica Aurelia (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the application of break-even point analysis, Margin of Safety and Operating Leverage value in Takoyaki Arone and Cemal Cemil Indah Depok MSMEs. The data used is primary data. The technique used in this study uses observation and interview methods using the Break Even Point (BEP) method. This study also considers other financial aspects related to the effectiveness of operational costs and product pricing strategies to increase competitiveness in the local market. The results of this study show that the implementation of Break Even Point carried out by Takoyaki Arone and Cemal Cemil Indah in determining profit is appropriate and has reached the BEP that should be, the value of the security level (MOS) in both MSMEs is at a safe limit when sales reach >80%, and the value of Operating Leverage in Takoyaki Arone and Cemal Cemil are both at the same level.  which is <2%. This finding also shows that both MSMEs have good financial resilience in facing sales fluctuations, although further strategies are needed to expand market share and optimize profits. The results of this study are expected to be a reference for other MSMEs in implementing simple financial analysis to improve the sustainability of their businesses.